(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The requirement for philosophical and methodological analysis of the foundations of human life caused actualization of philosophical and anthropological issues in modern education, that is, creating an utterly generic and holistic image of man and the corresponding educational model as a method of forming anthropological knowledge that would contribute to the preservation of the ontological unity of the world and its axiological rootedness . In this research most meaningful express of understanding of idea of man is presented in Greek philosophy. The picture, character, idea or model of man, presented in Greek philosophy, is beginning of understanding of man in history of western philosophical idea through that looks integrity of man as an ideal aim of systematization of efforts of philosophical anthropology.